Improvement of Clinical Outcomes of Total Aortic Arch Replacement and Frozen Elephant Trunk Surgery With Aortic Balloon Occlusion - Wang, Luchen; Cheng, Zeyi; Li, Yunfeng; Li, Junpeng; Guo, Hongwei; Liang, Shenghua; Sun, Xiaogang (Frontiers in Cardiovascular Medicine, 2021)
Background: Total aortic arch replacement (TAR) with frozen elephant trunk (FET) surgery provides improved long-term results, but the surgery itself is associated with higher risks compared with isolated proximal reconstructions. We applied an aortic balloon occlusion (ABO) technique to reduce the circulatory arrest (CA) time and improve other clinical outcomes. Methods: All patients who underwent TAR with FET surgery (130 with ABO technique, 230 with the conventional approach) in Fuwai Hospital from August 2017 to February 2019 were reviewed in this retrospective observational cohort study. Intra- and early-postoperative results and clinical characteristics were analyzed. Results: After 1:1 propensity score matching (130 cases in each group), the 30-day mortality of the ABO group and the conventional group were 4.6% and 10.8% (P=0.063), respectively. Although the reduction in complications was not statistically significant, the complication rate in the ABO group was relatively low, having fewer cases of postoperative renal (23.1% vs 38.5%, P=0.007) and hepatic (12.3% vs 30.0%, P<0.001) injury, lower postoperative wake-up time (15.2±23.6 h vs 20.1±26.5 h, respectively, P<0.001), reduced chest tube output (176.03±143.73 ml vs 213.29±130.12 ml, respectively, P=0.003), lower red blood cell (RBC) transfusion volume (4.98±6.53 u vs 7.28±10.41 u, respectively, P=0.008), and no fatal events. Conclusions: The ABO technique is a simple method that can reduce the CA time and improve the recovery stage following TAR with FET surgery. The technique represents a practical strategy to treat patients with high operative risks due to its lower complication rate compared to the conventional approach.